Pelatihan Kader Penegak Disiplin Protokol Kesehatan Tanggap Covid-19 SDIT Harapan Umat Jember - Elly Nurus Sakinah; Abu Khoiri; Jauhar Firdaus (Indonesian Journal Publisher, 2022)
The COVID-19 pandemic condition presents its own difficulties in achieving this competency for students. Learning from home has several limitations so that the Government of Indonesia through the Indonesian Ministry of Education allows the school learning process offline or face-to-face. This requires readiness from schools in implementing health protocols in a disciplined manner to reduce the risk of transmission of covid 19. Supervision of the enforcement of health protocols will be very difficult if you only rely on health workers. The Hope Integrated Islamic Elementary School (SDIT Harum) Jember will now start limited face-to-face learning in order to fulfill the competence of students. The Faculty of Medicine and the Faculty of Public Health, University of Jember have a moral responsibility to provide education and health promotion activities to the surrounding community, one of which is basic education institutions. One solution that can be done is to form cadres who are tasked with enforcing the implementation of health protocols in a disciplined manner. The hope of this program is that this health protocol discipline enforcer cadre can become an extension of health workers in promoting the importance of health protocol discipline as the main pillar of preventing COVID 19 in limited face-to-face learning.